Characterizing graphene-modified electrodes for interfacing with Arduino®-based devices - Arris, Farrah Aida; Ithnin, Mohamad Hafiz; Wan Salim, Wan Wardatul Amani (IEEE, 2016)
Portable low-cost platform and sensing systems for identification and quantitative measurement are in high demand for various environmental monitoring applications, especially in field work. Quantifying parameters in the field requires both minimal sample handling and a device capable of performing measurements with high sensitivity and stability. Furthermore,the one-device-fits-all concept is useful for continuous monitoring of multiple parameters. Miniaturization of devices can be achieved by introducing graphene as part of the transducer in an electrochemical sensor. In this project, we characterize graphene deposition methods on glassy-carbon electrodes (GCEs) with the goal of interfacing with an Arduino-based user-friendly microcontroller. We found that a galvanostatic electrochemical method yields the highest peak current of 10 mA, promising a highly sensitive electrochemical sensor. An Atlas Scientific™ printed circuit board (PCB) was connected to an Arduino® microcontroller using a multi-circuit connection that can be interfaced with graphene-based electrochemical sensors for environmental monitoring.